DEVELOPMENT OF A STEAM-BASED DIGITAL LEARNING MODEL IN SOCIAL STUDIES TO ENHANCE CRITICAL THINKING SKILLS OF PHASE D STUDENTS - Muliana, Muliana; Fadhilah, Fadhilah; Aziz, Abdul; Azwir, Azwir; Mahyuna, Mahyuna (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
The dominance of conventional pedagogical approaches that are textual and monodisciplinary in Social Sciences (IPS) learning often hinders the development of students' higher-order thinking skills in the era of the industrial revolution 4.0. This study aims to develop a valid, practical, and effective STEAM (Science, Technology, Engineering, Arts, and Mathematics)-based digital learning model to improve Phase D students' critical thinking skills. This study applies the modified Borg & Gall Research and Development (R&D) method, including the stages of needs analysis, design planning, expert validation, and limited trials on grade VIII students. The results showed that the developed model met the criteria of very valid with an expert validation score reaching 92.6% and a practicality level of 88.4%. Quantitatively, the effectiveness of the model was proven significant through a t-test (p < 0.05) with an increase in the N-gain score of 0.67 which is classified as medium to high category, where the average critical thinking ability increased from 37.5% to 71.25%. The main conclusion of this study confirms that the integration of the STEAM transdisciplinary approach with digital technology is able to transform social studies learning to be more contextual, holistic, and adaptive, so it is recommended as a strategic solution in strengthening students' analytical and evaluative competencies according to the demands of the 21st century curriculum. ABSTRAK Dominasi pendekatan pedagogis konvensional yang bersifat tekstual dan monodisiplin dalam pembelajaran Ilmu Pengetahuan Sosial (IPS) sering kali menghambat pengembangan keterampilan berpikir tingkat tinggi siswa di era revolusi industri 4.0. Penelitian ini bertujuan mengembangkan model pembelajaran digital berbasis STEAM (Science, Technology, Engineering, Arts, and Mathematics) yang valid, praktis, dan efektif untuk meningkatkan kemampuan berpikir kritis siswa Fase D. Penelitian ini menerapkan metode Research and Development (R&D) model Borg & Gall yang dimodifikasi, meliputi tahapan analisis kebutuhan, perancangan desain, validasi ahli, serta uji coba terbatas pada siswa kelas VIII. Hasil penelitian menunjukkan bahwa model yang dikembangkan memenuhi kriteria sangat valid dengan skor validasi ahli mencapai 92,6% dan tingkat kepraktisan 88,4%. Secara kuantitatif, efektivitas model terbukti signifikan melalui uji-t (p < 0,05) dengan peningkatan skor N-gain sebesar 0,67 yang tergolong kategori sedang hingga tinggi, di mana rata-rata kemampuan berpikir kritis meningkat dari 37,5% menjadi 71,25%. Kesimpulan utama studi ini menegaskan bahwa integrasi pendekatan transdisipliner STEAM dengan teknologi digital mampu mentransformasi pembelajaran IPS menjadi lebih kontekstual, holistik, dan adaptif, sehingga direkomendasikan sebagai solusi strategis dalam memperkuat kompetensi analitis dan evaluatif siswa sesuai tuntutan kurikulum abad ke-21.